DuoBody-CD40x4-1BB induces dendritic-cell maturation and enhances T-cell activation through conditional CD40 and 4-1BB agonist activity. Issue 6 (10th June 2022) - Muik, Alexander; Adams III, Homer C; Gieseke, Friederike; Altintas, Isil; Schoedel, Kristina B; Blum, Jordan M; Sänger, Bianca; Burm, Saskia M; Stanganello, Eliana; Verzijl, Dennis; Spires, Vanessa M; Vascotto, Fulvia; et al.
Abstract : Background: Despite the preclinical promise of CD40 and 4-1BB as immuno-oncology targets, clinical efforts evaluating CD40 and 4-1BB agonists as monotherapy have found limited success. DuoBody-CD40×4-1BB (GEN1042/BNT312) is a novel investigational Fc-inert bispecific antibody for dual targeting and conditional stimulation of CD40 and 4-1BB to enhance priming and reactivation of tumor-specific immunity in patients with cancer. Methods: Characterization of DuoBody-CD40×4-1BB in vitro was performed in a broad range of functional immune cell assays, including cell-based reporter assays, T-cell proliferation assays, mixed-lymphocyte reactions and tumor-infiltrating lymphocyte assays, as well as live-cell imaging. The in vivo activity of DuoBody-CD40×4-1BB was assessed in blood samples from patients with advanced solid tumors that were treated with DuoBody-CD40×4-1BB in the dose-escalation phase of the first-in-human clinical trial (NCT04083599 ). Results: DuoBody-CD40×4-1BB exhibited conditional CD40 and 4-1BB agonist activity that was strictly dependent on crosslinking of both targets. Thereby, DuoBody-CD40×4-1BB strengthened the dendritic cell (DC)/T-cell immunological synapse, induced DC maturation, enhanced T-cell proliferation and effector functions in vitro and enhanced expansion of patient-derived tumor-infiltrating lymphocytes ex vivo. The addition of PD-1 blocking antibodies resulted in potentiation of T-cell activation and effector functions in vitro compared with either monotherapy, providing combination rationale. Furthermore, in a first-in-human clinical trial, DuoBody-CD40×4-1BB mediated clear immune modulation of peripheral antigen presenting cells and T cells in patients with advanced solid tumors. Conclusion: DuoBody-CD40×4-1BB is capable of enhancing antitumor immunity by modulating DC and T-cell functions and shows biological activity in patients with advanced solid tumors. These findings demonstrate that targeting of these two pathways with an Fc-inert bispecific antibody may be an efficacious approach to (re)activate tumor-specific immunity and support the clinical investigation of DuoBody-CD40×4-1BB for the treatment of cancer.